Exceptional improvement in chronic stroke through Guided Self-rehabilitation Contract: a case report study - Gault-Colas, Caroline; Pradines, Maud; Baude, Marjolaine; Gracies, Jean-Michel (Frontiers in Rehabilitation Sciences, 2024)
A 44-year-old woman suffered a carotid dissection causing a deep and superficial right middle cerebral artery stroke in October 2013, despite undergoing thrombolysis and thrombectomy. Sixteen months later, massive left upper extremity impairment persisted. She then agreed to embark upon a guided self-rehabilitation contract (GSC). This GSC is a moral contract where the physician or therapist identifies specific muscles, particularly hypo-extensible and disabling that act as antagonists to functional activities. The physician or therapist then teaches and prescribes quantified daily high-load self-stretch postures for these muscles, alternating with repeated maximal amplitude movement exercises against their resistance. In turn, the patient commits to practicing the prescribed program and to delivering a diary of the stretch postures and alternating movement exercises performed each day. Over 4 years of GSC, the patient practiced upon prescription against a total of seven upper limb antagonists to common functional movements: shoulder extensors, shoulder internal rotators, elbow flexors, elbow pronators, wrist and finger flexors, and interossei muscles. She manually filled up her diary 99% of the days. Each day, she practiced an average of 20 min of high-load static self-stretch per muscle, alternating with about 50 maximal active efforts against the resistance of each targeted muscle's resistance. Overall, her mean static self-stretch time was 81 ± 2 (mean ± SEM) min/day, and her mean number of active maximal efforts was 285 ± 78/day, for a total daily self-rehabilitation time of over 2 h a day. Five years after her stroke, she had recovered all left upper extremity use in daily activities and resumed her previous job as a nurse's aide. She now spontaneously uses her left hand in most tasks. Functional MRI (March 2020) demonstrated bilateral primary motor and motor supplementary area activation upon left-hand exercise. Prolonged static self-stretch increased muscle extensibility (muscle plasticity) while maximal amplitude, alternating movement training reduced co-contraction in these muscles (neural plasticity). The Modified Frenchay Scale assessment was video-recorded by the clinician at each visit, allowing qualitative and quantitative evaluation of the functional capacities. The two videos of the first and last clinic visits have been uploaded and are available.